Teaching Children in the Instruction of Amenemope and Deuteronomy - Awabdy, Mark A. (Vetus Testamentum, 2015)
The Instruction of Amenemope and the book of Deuteronomy share a common conviction about the nature and intent of parental teaching. This commonality is marked by basic lexical analogues, as well as three conceptual analogues from the broader contexts of the two compositions. Consequently, this study provides further evidence for the claim that Deuteronomy evinces wisdom influence.